(untitled) (Bulletin of Pure and Applied Sciences-Chemistry, 2021)
Cassia singueana is a medicinal plant used in Northern Nigeria for the treatment and management of ailments which include ulcer, as diuretic, acute malaria, sooth stomach spasm, cure abdominal pain etc. This research study aimed to analyse the phytochemical content and evaluate the acute and antidiarrhoeal activity of the leaf of Cassia singueana. Fresh stem bark of the plant was air-dried, extracted using methanol and screened for phytochemicals. Acute toxicity of the crude methanol extract was evaluated using Lorke’s method, while the antidiarrhoeal study was carried out using castor oil-induced diarrhoea, gastrointestinal meal transit of charcoal meal and castor oil-induced enteropooling. The crude methanol stem bark extract revealed the presence of carbohydrate, cardiac glycoside, steroid, saponins, flavonoids and terpenes. The extract had oral and i.pLD50 of ≥ 5000 mg/kg and 2150mg/kg respectively. It alsoproduced a marked anti-diarrhoeal effect in rats. Extract doses at 200 mg/kg, 400 mg/kg, 800 mg/kg, exhibited % protection of 28, 53.30, 69.33against faeces produced upon administration of castor oil; it also slowed down the propulsion of charcoal meal through the gastrointestinal tract with % inhibition of 37.81, 60.09 and 76.60; as well as the extract significantly decreased intestinal fluid with % protection of 48.50, 38.80 and 22.30 volume in rats, when compared to standard antidiarrhoeal drug, loperamide (94.60 %) at 3 mg/kg, atropine (92.50 %) at 3 mg/kg and loperamide (15.90 %) at 3 mg/kg respectively. Thus, the methanol extracts of Cassia singueana exhibit anti-diarrhoeal properties, which may be due to the presence of phytochemicals. This study justifies its ethno-medicinal use in the treatment of diarrhoea.